The technology of nonviolence social media and violence prevention - Bock, Joseph G. (MIT Press, 2012)
How technology and community organizing can combine to help prevent violence, with examples from Chicago to Sri Lanka.
Keywords: Nonviolence.; Violence -- Prevention.; Social media.; elektronické knihy; electronic books